Ambiente familiar y logros de aprendizaje en ciencias sociales en estudiantes de secundaria de la Institución Educativa Miguel Acosta Oyarce, Caballococha 2025 - Gutierrez Sinarahua, Marlys Ursulita (2026)
The study aimed to determine the relationship between the family environment and learning achievement in Social Sciences among secondary school students at the Miguel Acosta Oyarce Educational Institution in Caballo Cocha. The research was basic, with a quantitative approach and a non-experimental, cross-sectional, descriptive-correlational design. The population consisted of 955 students, from which a probabilistic sample of 275 was selected. Two Likert-scale questionnaires were applied to measure the family environment and learning achievement. The results revealed a strong and significant positive correlation between both variables (Spearman's Rho = 0.786; p < 0.001). Analysis by dimensions showed that development (Rho=0.709) and stability (Rho=0.696) presented strong positive correlations, while the relationships dimension (Rho=0.584) showed a moderate positive correlation. It was concluded that a significant relationship exists between a favorable family environment and better learning achievement in Social Sciences.